Globalization and Politics in India - Baldev Raj Nayar (Ed.) (New Delhi Oxford University Press, 2007)
This volume-in the Themes in Politics series-asks three important questions: What is the nature of the phenomenon under study? What are the causes of this pattern or phenomenon? What are its consequences? In addition, it asks what policies that would accentuate or attenuate the consequences? These questions form the overarching framework of this reader. The introduction provides a broad overview of the nature and development of economic globalization and India's experience with it. The readings offer a wide range of viewpoints and are organized into five broad sections: the nature of globalization, both in its past and contemporary incarnations; the nature of economic strategy in India that preceded globalization; the shift to economic liberalization and the stimulus for it; the consequences of globalization and liberalization for India in relation to its external setting; and the consequences of these processes for India's domestic situation.
Includes bibliographical references and index
Keywords: International economics; Globalization -- India; Politics -- India; Economics; Political Science